2008
DOI: 10.1111/j.1863-2378.2007.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gastrointestinal Bacterial Pathogens in a Population of Zoo Animals

Abstract: Faecal prevalence of gastrointestinal bacterial pathogens, including Campylobacter, Escherichia coli O157:H7, Salmonella, Shigella, Yersinia, as well as Arcobacter, were examined in 317 faecal specimens from 44 animal species in Belfast Zoological Gardens, during July-September 2006. Thermophilic campylobacters including Campylobacter jejuni, Campylobacter coli and Campylobacter lari, were the most frequently isolated pathogens, where members of this genus were isolated from 11 animal species (11 of 44; 25%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 5 publications
0
13
1
Order By: Relevance
“…In one of these studies, the histological examination of the enteric tissues of the infected animals revealed a chronic active colitis (7). In other cases, the strains recovered showed a strong resistance to antibiotics (63,141). Despite these data, the significance of arcobacters as a pathogen in nonhuman primates has yet to be determined.…”
Section: Arcobacter In Animalsmentioning
confidence: 98%
See 1 more Smart Citation
“…In one of these studies, the histological examination of the enteric tissues of the infected animals revealed a chronic active colitis (7). In other cases, the strains recovered showed a strong resistance to antibiotics (63,141). Despite these data, the significance of arcobacters as a pathogen in nonhuman primates has yet to be determined.…”
Section: Arcobacter In Animalsmentioning
confidence: 98%
“…In several studies A. butzleri has so far been the only species isolated both from healthy nonhuman primates (131,141,164) and from those with diarrhea (7,63,92). In one of these studies, the histological examination of the enteric tissues of the infected animals revealed a chronic active colitis (7).…”
Section: Arcobacter In Animalsmentioning
confidence: 99%
“…A number of studies have been focused on MDR Escherichia coli derived from humans, wild, domesticated or food animals and from the environment (Literak et al ., ; Dolejska et al ., , b; Platell et al ., ). Captive animals in zoological gardens can serve as a reservoir of antibiotic‐resistant pathogenic bacteria such as Campylobacter spp., Salmonella spp., Yersinia spp., and pathogenic E. coli strains (Gopee et al ., ; Stirling et al ., ). A high frequency of resistance including ESBL production and the presence of PMQR genes was found in E. coli isolated from zoo animals in Japan and China (Ahmed et al ., ; Wang et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…A. butzleri has been the only Arcobacter spp. isolated from both diarrheic as well as healthy nonhuman primates (Wesley et al 2003;Stirling et al 2008). Microscopic examination of the intestines from these non-human primates revealed chronic active colitis (Anderson et al 1993).…”
Section: Epidemiology and Transmission In Animalsmentioning
confidence: 99%